Structural Equation Modelling (SEM) Based Assessment Of Students’ M-Learning Behavioural Adoption Using An Extended-Simplified TAM - Kalsi, Dr. Parveen Singh; Kaur, Rajveer (Migration Letters, 2024)
In today’s highly globalised world, m-learning provides learners with a novel avenue for acquiring knowledge, allowing them to access any information anywhere according to their time schedule. Despite its portability and speed, m-learning adoption is relatively in its infancy stage in developing nations across the globe. The Technology Adoption Model (TAM) for end-user technology adoption has been the subject of research over the last decades. Despite this, empirical literature related to TAM usage in the educational domain is very limited. Thus, this research endeavours to utilise an extended-simplified TAM framework using a quantitative and cross-sectional approach to analyse the m-learning behavioural intentions of graduate and undergraduate pupils attending private universities in the state of Punjab, India. The research study employed AMOS 21 to conduct SEM based analysis in order to validate the constructed hypotheses through data collected from 392 students. Findings ascertained that perceived usefulness favourably affects students’ m-learning attitudes and behavioural intentions. Perceived ease of use and enjoyment positively affect students’ attitudes for m-learning. Additionally, the study found that attitude towards use positively affects behavioural intentions, which in turn positively affects students’ m-learning system utilisation.